PERUBAHAN JUMLAH KONSUMEN RITEL TRADISIONAL SETELAH ADANYA RITEL MODEREN DI KECAMATAN SUMBAWA - Suarantalla, Ryan; Hermanto , Koko (Jurnal TAMBORA, 2020)
In Sumbawa sub-district, West Nusa Tenggara (NTB) province now hasmany standing modern retail shops (Indomaret, Alfamart). However there isother sub-districts in the province of NTB prohibit modern retailers from operating,with consideration of the influence on the existence of a grocery store (retailtraditional). Therefore the aim of this study is to analyze whether there is anychanges in the number of consumers in traditional retail before and after retailmodern in Sumbawa sub-district. The sample used in this studyare residents of Sumbawa sub-district. This study uses an approachquantitative by statistical analysis. The data used in this study arePrimary data, which is obtained through distributing questionnaires to the sample. Knownthe population of the Sumbawa sub-district based on data from the Regency Statistics AgencySumbawa in 2018 is 61,518 people, so using the formulaSlovin, the number of samples that must take the questionnaire for this study is minimal100 people (with an error rate of 10%) were selected by random sampling. Methodwhich is used to achieve the objectives of this study is to use the sign testand SPSS assistance. The analysis results show that the existence of modern retailers inSumbawa sub-district lowered the number of consumers who shop at traditional retail.